2024
DOI: 10.1186/s40164-024-00500-y
|View full text |Cite
|
Sign up to set email alerts
|

Heat-killed Prevotella intermedia promotes the progression of oral squamous cell carcinoma by inhibiting the expression of tumor suppressors and affecting the tumor microenvironment

Yifan Zhou,
Yao Qin,
Jingjing Ma
et al.

Abstract: Background Oral microbial dysbiosis contributes to the development of oral squamous cell carcinoma (OSCC). Our previous study showed that Prevotella intermedia (P. intermedia) were enriched in the oral mucosal surface, plaque, and saliva of patients with OSCC. Intratumoral microbiome could reshape the immune system and influence the development of various tumors. However, the invasion status of human OSCC tissues by P. intermedia and the pathway through which intratumoral P. intermedia potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In another study, it was found that the detection rate of P. intermedia in the oral cavity of patients with both OLP and periodontal disease was significantly higher than in those with only periodontal disease [ 48 ]. Recently, P. intermedia has been found to potentially inhibit the expression of tumor suppressors, alter the tumor microenvironment, and promote the progression of OSCC [ 49 ]. These studies suggest a potential correlation between P. intermedia and the pathogenic mechanisms of NEOLP.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was found that the detection rate of P. intermedia in the oral cavity of patients with both OLP and periodontal disease was significantly higher than in those with only periodontal disease [ 48 ]. Recently, P. intermedia has been found to potentially inhibit the expression of tumor suppressors, alter the tumor microenvironment, and promote the progression of OSCC [ 49 ]. These studies suggest a potential correlation between P. intermedia and the pathogenic mechanisms of NEOLP.…”
Section: Discussionmentioning
confidence: 99%